The Role of Cultural Attributes in Inequality and Poverty - Malul, Miki; Shoham, Amir; Zolotoy, Leon (Journal of Income Distribution®, 2010)
This article uses cross-country data to explore the role of cultural attributes in the inequality of income distribution and poverty within countries. Using the Hofstede cultural dimensions, we found that individualism is negatively correlated with the Gini index and the poverty ratio. We also found that the lower the status of women in a society, the higher the level of poverty in that society. Furthermore, we found that adding the cultural variables into the analysis significantly improves the ability to explain the differences in inequality and poverty in different countries.